Ameliorative effect of naringin against doxorubicin-induced acute cardiac toxicity in rats. (2nd April 2016) - Kwatra, Mohit; Kumar, Vikas; Jangra, Ashok; Mishra, Murli; Ahmed, Sahabuddin; Ghosh, Pinaki; Vohora, Divya; Khanam, Razia
Abstract: Context : Doxorubicin (Dox) is one of the most active chemotherapeutic agents used to treat various types of cancers. Its clinical utility is compromised due to fatal cardiac toxicity characterized by an irreversible cardiomyopathy. Objective : This study evaluates the cardioprotective potential of naringin (NR) against Dox-induced acute cardiac toxicity in rats. Materials and methods : Male Wistar rats were randomly divided into five groups. NR (50 and 100 mg/kg) was administered intraperitoneally (i.p.) daily from 0 to 14 d. Doxorubicin (15 mg/kg, i.p.) was given as a single dose on the 10th day. On the 14th day, all animals were sacrificed and oxidative stress parameters that include malondialdehyde (MDA), glutathione (GSH) level, superoxide dismutase (SOD), catalase (CAT) activities, and all mitochondrial complexes (I-IV) activities were evaluated along with histopathological studies of the heart. Results : Doxorubicin-induced cardiotoxicity was confirmed by increased ( p  < 0.05) MDA, decreased ( p  <  0.05 ) GSH levels, SOD, and CAT activities, mitochondrial complexes (I–IV) activities in the heart tissue. NR (100 mg/kg) showed cardioprotection as evident from significant decreased MDA ( p  < 0.001) level, raised ( p  <  0.001 ) GSH level, SOD and CAT activities and increased mitochondrial complexes I ( p  < 0.01), II ( p  < 0.001), III ( p  < 0.001), and IV ( p  < 0.05) activities. Further, Dox-induced cardiotoxicity was confirmed by histopathological studies. These obtained results indicated the protective role of NR against Dox-induced cardiac toxicity in rats. Conclusion : NR can be used in combination with Dox due to its high cardioprotective effect against Dox-induced cardiomyopathy.